Rock stiffness measurements fibre Bragg grating sensor (FBGs) and the effect of cyanoacrylate and epoxy resin as adhesive materials - Isah, B.W. (Ain Shams University, 2021)
This study investigates the influence of adhesive type and its thickness performance when a highly sensitive Fibre Bragg grating (FBG) sensor is used to determine the stiffness properties of rock and cementitious material. Laboratory uniaxial tests were conducted on limestone and cement-paste specimens, equipped with strain gauges and FBGs attached locally using cyanoacrylate and epoxy-based adhesives. Differences were observed in the FBGs measured strains and the calculated elastic parameters between sensors attached with cyanoacrylate and epoxy-based on the same material (rock and cement). Smaller changes in strain are observed when FBG is attached with cyanoacrylate. Finite Element modelling indicated a reduction in peak strain and increase in Young's modulus from FBG compared to the rock when the adhesive thickness is increased. Also, the strain and stiffness determined vary with the adhesive type. Cyanoacrylate adhesive is relatively more suitable as it gives FBG strain values closer to that of the rock as opposed to Epoxy. Â© 2020 THE AUTHORS